2022
DOI: 10.3389/feduc.2022.846567
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Video-Assisted Collaborative Reflections of Socio-Emotional Experiences During Teaching Practicum

Abstract: This study explores video as a tool for student teachers in reflecting upon their own teaching practice. The particular interest is in exploring, what kind of socio-emotional experiences did the student teachers describe during the video-assisted collaborative reflection and what benefits student teachers experienced through the video-assisted collaborative reflections? The study implements a video-observation model (Participatory and Empowering Video Analysis- model, PEVA™) developed for a professional teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Currently, most studies that incorporate feedback elements into multimedia learning environments only provide simple feedback or basic prompts to guide learners through the learning process, without considering more complex feedback or providing opportunities for reflection (Sun et al, 2023; Yorganci, 2022). Based on the investigation, although many studies have identified that feedback can provide opportunities for reflection and promote learner engagement, achievement, and the development of higher‐order thinking (Alazmi, 2023; Näykki et al, 2022), it remains unclear whether these effects can be achieved in VR learning environments. In light of this, the aim of this study is to investigate whether providing learners with opportunities for reflection on feedback in the VR learning environment can also lead to the promotion of higher‐order thinking among learners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, most studies that incorporate feedback elements into multimedia learning environments only provide simple feedback or basic prompts to guide learners through the learning process, without considering more complex feedback or providing opportunities for reflection (Sun et al, 2023; Yorganci, 2022). Based on the investigation, although many studies have identified that feedback can provide opportunities for reflection and promote learner engagement, achievement, and the development of higher‐order thinking (Alazmi, 2023; Näykki et al, 2022), it remains unclear whether these effects can be achieved in VR learning environments. In light of this, the aim of this study is to investigate whether providing learners with opportunities for reflection on feedback in the VR learning environment can also lead to the promotion of higher‐order thinking among learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there has been limited investigation into the effects of providing feedback for reflection and its impact on higher-order thinking within current VR-based training and learning environments (Lai et al, 2021;Marinelli et al, 2023;Wang, Cheng, et al, 2023). While reflection has been proven effective in promoting engagement and learning achievement in various learning activities (Alazmi, 2023;Näykki et al, 2022), its effects in VR remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Falter and Barnes (2020) and Sturkie (2017), in this reflection process how these students feel should not be masked as reflective teaching has positive contribution to teacher intellect and emotion. Within this respect, in these teacher education programs, curriculum decisions need to take into consideration the educational strategies that promote teacher candidates' "emotional sharing and regulation" (Näykki et al, 2022). However, despite its reported value and being integral part of many teacher training programs, still there exists confusion regarding the definition of reflection, its scope, and application in the preparation of teacher candidates.…”
Section: Introductionmentioning
confidence: 99%